Cold tolerance of third-instar Drosophila suzukii larvae. (January 2017) - Jakobs, Ruth; Ahmadi, Banafsheh; Houben, Sarah; Gariepy, Tara D.; Sinclair, Brent J.
Graphical abstract: Highlights: Drosophila suzukii wandering and feeding larvae are chill susceptible. D. suzukii larvae develop slowly into larger adults under fluctuating temperatures. Rearing under fluctuating temperatures improves prolonged cold tolerance. Acute cold tolerance was not phenotypically plastic. Abstract: Drosophila suzukii is an emerging global pest of soft fruit; although it likely overwinters as an adult, larval cold tolerance is important both for determining performance during spring and autumn, and for the development of temperature-based control methods aimed at larvae. We examined the low temperature biology of third instar feeding and wandering larvae in and out of food. We induced phenotypic plasticity of thermal biology by rearing under short days and fluctuating temperatures (5.5–19 °C). Rearing under fluctuating temperatures led to much slower development (42.1 days egg-adult) compared to control conditions (constant 21.5 °C; 15.7 days), and yielded larger adults of both sexes. D. suzukii larvae were chill-susceptible, being killed by low temperatures not associated with freezing, and freezing survival was not improved when ice formation was inoculated externally via food or silver iodide. Feeding larvae were more cold tolerant than wandering larvae, especially after rearing under fluctuating temperatures, and rearing under fluctuating temperatures improved survival of prolonged cold (0 °C) to beyond 72 h in both larval stages. There was no evidence that acute cold tolerance could be improved by rapid cold-hardening. We conclude that D. suzukii has the capacity to develop at low temperatures under fluctuating temperatures, but that they have limited cold tolerance. However, phenotypic plasticity of prolonged cold tolerance must be taken into account when developing low temperature treatments for sanitation of this species.